گاما رو نصب کن!

{{ number }}
اعلان ها
اعلان جدیدی وجود ندارد!
کاربر جدید

جستجو

پربازدیدها: #{{ tag.title }}

میتونی لایو بذاری!

حاصل عبارت $ I=\frac{\sqrt[4]{(-3+\sqrt{2})^4}-\sqrt[6]{(1-\sqrt{2})^6}}{2-\sqrt{2}} $ با کدام گزینه برابر است؟

1 ) 

$ \frac{2}{2-\sqrt{2}} $

2 ) 

2

3 ) 

$ \frac{2\sqrt{2}-3}{2-\sqrt{2}} $

4 ) 

2-

پاسخ تشریحی :
نمایش پاسخ

$ \sqrt{2} \lt 3 \Rightarrow \sqrt[4]{(-3+\sqrt{2})^4} = | -3 + \sqrt{2} | = 3 - \sqrt{2} \\ 1 \lt \sqrt{2} \Rightarrow 1- \sqrt{2} \lt 0 \Rightarrow \sqrt[6]{(1-\sqrt{2})^6} = | 1-\sqrt{2} | = -1+\sqrt{2} $

$ =3-\sqrt{2} - (-1+\sqrt{2})=3-\sqrt{2}+1-\sqrt{2} = 4-2\sqrt{2} $صورت کسر

$ I=\frac{4-2\sqrt{2}}{2-\sqrt{2}} = \frac{2(2-\sqrt{2})}{2-\sqrt{2}}=2 $

تحلیل ویدئویی تست

سکینه باقری فرد